ANALISIS HASIL FERMENTASI PEMBUATAN BIOETANOL DENGAN VARIASI WAKTU MENGGUNAKAN BAHAN (SINGKONG, BERAS KETAN HITAM DAN BERAS KETAN PUTIH) - Andrie Yeremia Marchelino Simanjuntak; Rachmat Subagyo (Scientific Journal of Mechanical Engineering Kinematika, 2019)
This study aims to determine the levels of bioethanol from (cassava, black sticky rice, and white sticky rice) with the addition of 10 grams of yeast mass, with a variation of fermentation time of 48 hours, 72 hours and 96 hours and knowing the ethanol levels in accordance with National Standards Indonesia (SNI). This research was carried out by hydrolysis or boiling of ingredients (cassava, black sticky rice, and white sticky rice) using 800 ml of distilled water with 30 minutes, then fermentation using yeast or (saccharomyces cereviseae) and distillation using a tool. Complete destilator to obtain ethanol from fermentation results which is then tested with a pen refractometer to determine whether or not ethanol is formed from the distillation process. The samples were then tested for ethanol content using the Gas Chromatography tool. The results of this study are known by conducting a test using the Gas Chromatography tool to determine the ethanol content contained in the distilled sample. The results of cassava ethanol content with 72 hours fermentation time with ethanol were 98.41%, black sticky rice with 96 hours fermentation time the ethanol content was 94.96%, and white sticky rice with 96 hours fermentation time the ethanol content was 96.67%.